The handbook of software for engineers and scientists - Ross, Paul W. 1938- (CRC Press ; IEEE Press, 1996)
Offers information on a variety of subjects such as common platforms and operating systems, applications programs, networking, and many other problem-solving tools that are necessary to effectively use computers on a daily basis. This book is suitable for practicing engineer and scientist in industry, and academia and a novice computer user.